Novel MenA Inhibitors Are Bactericidal against Mycobacterium tuberculosis and Synergize with Electron Transport Chain Inhibitors - Berube, Bryan J. (Antimicrob Agents Chemother, 2019)
Mycobacterium tuberculosis is the leading cause of morbidity and death resulting from infectious disease worldwide. The incredible disease burden, combined with the long course of drug treatment and an increasing incidence of antimicrobial resistance among M. tuberculosis isolates, necessitates novel drugs and drug targets for treatment of this deadly pathogen. Recent work has produced several promising clinical candidates targeting components of the electron transport chain (ETC) of M. tuberculosis, highlighting this pathway’s potential as a drug target. Menaquinone is an essential component of the M. tuberculosis ETC, as it functions to shuttle electrons through the ETC to produce the electrochemical gradient required for ATP production for the cell. We show that inhibitors of MenA, a component of the menaquinone biosynthetic pathway, are highly active against M. tuberculosis. MenA inhibitors are bactericidal against M. tuberculosis under both replicating and nonreplicating conditions, with 10-fold higher bactericidal activity against nutrient-starved bacteria than against replicating cultures. MenA inhibitors have enhanced activity in combination with bedaquiline, clofazimine, and inhibitors of QcrB, a component of the cytochrome bc(1) oxidase. Together, these data support MenA as a viable target for drug treatment against M. tuberculosis. MenA inhibitors not only kill M. tuberculosis in a variety of physiological states but also show enhanced activity in combination with ETC inhibitors in various stages of clinical trial testing.